Urban sources of synthetic musk compounds to the environment. Issue 1 (21st December 2018) - Wong, Fiona; Robson, Matthew; Melymuk, Lisa; Shunthirasingham, Chubashini; Alexandrou, Nick; Shoeib, Mahiba; Luk, Edmund; Helm, Paul; Diamond, Miriam L.; Hung, Hayley
Abstract : Synthetic musk compounds found in ambient air and surface tributary waters may due to emissions from indoor air and release from wastewater treatment plant. Abstract : The occurrence and potential sources of synthetic musk compounds (SMCs) in the urban and surrounding environment were investigated. We analyzed air, soils and surface waters from a wide array of land-use types and urban densities including air from wastewater treatment plants (WWTPs), indoor, urban, rural, and remote Arctic sites; surface waters from urban and rural tributaries; and effluents of three WWTPs. In air, the median sum concentration of six selected polycyclic musks (Σ6 PCMs) ( i.e., galaxolide, tonalide, cashmeran, celestolide, phantolide, traseolide) were the highest from WWTP on-site > indoor > urban > WWTP off-site > rural. SMCs were not found in remote Arctic air indicating low potential for long-range atmospheric transport. SMCs were not found in soils, likely because of their high volatility and fast biodegradation rate. Galaxolide (HHCB) and tonalide (AHTN) were the two most abundant SMCs in air, tributaries and WWTP effluents. Σ6 PCM concentrations in air taken along urban–rural transects and in tributary water were positively correlated with population density. In WWTP on-site air, trace levels of the toxic nitro-musks, namely musk xylene and musk ketone were detected and macrocyclic musks accounted for ∼10% of the total SMCs measured. In WWTP effluents, the concentrations of Σ6 PCMs were proportional to the population served. We conclude that sources of SMCs to the outdoor urban environment and hence the surrounding region, originate from releases from indoor air, and temperature-dependent volatilization from WWTPs during treatment.